Синтез структури пристрою для технічного діагостування прискорювача трамвая - Грабко, В. В.; Шевчук, Юрій Володимирович; Базалицький, Вадим Павлович; Солонінко, Максим Аркадійович (НТУ "ХПІ", 2010)
In work the structure of the tram accelerator diagnostic device is synthesized agrees with developed before mathematical model. In device structure possibility of automatic diagnosing of all characteristic malfunctions in the course of tram movement is considered. The synthesized structure of the device in difference from the existing allows to define malfunction at any moment of device work, possesses, the best indicators of reliability at the expense of scheme elements reduction quantity.
Synthesis of structure for tram accelerator technical diagnosting
Keywords: транспорт громадський; склад електрорухомий; модель математична